The receptor for advanced glycation end-products (RAGE) plays a key role in the formation of nanotubes (NTs) between peritoneal mesothelial cells and in murine kidneys - Ranzinger, Julia; Rustom, Amin; Heide, Danijela; Morath, Christian; Schemmer, Peter; Nawroth, Peter Paul; Zeier, Martin; Schwenger, Vedat (Cell & tissue research, 2014)
The receptor for advanced glycation end-products (RAGE), a multiligand receptor of the immunoglobulin superfamily, takes part in various inflammatory processes. The role of this receptor in the context of intercellular communication, like nanotube (NT)-mediated interaction, is largely unknown. Here, we use cell cultures of human and murine peritoneal mesothelial cells as well as murine kidneys from wild-type and RAGE knockout mouse models to assess the role of RAGE in NT formation and function. We show that loss of RAGE function results in reduced NT numbers under physiological conditions and demonstrate the involvement of MAP kinase signaling in NT formation. Additionally, we show for the first time the existence of NTs in murine kidney tissue and confirm the correlation of RAGE expression and NT numbers. Under elevated oxidative stress conditions like renal ischemia or peritoneal dialysis, we demonstrate that RAGE absence does not prevent NT formation. Rather, increased NT numbers and attenuated kidney tissue damage could be observed, indicating that, depending on the predominant conditions, RAGE affects NT formation with implications for cellular communication.